Adobe Flash CS3 - Gonzalez, James; Virtual Training Company ([Australia] : Virtual Training Company, 2008)
In this tutorial, the author applies his flash expertise and many years of training experience to present step-by-step demonstrations and instructions covering a wide range of Flash animation and authoring techniques
Title from container
Trainig CD
Contains 125 movies with total time 11 hours
System requirements: Mac: System 9 or higher ; PC: Windows 98 or higher, 32MB System RAM, 6MB Video RAM, 16x CD-ROM ; QuickTime 6
Keywords: Flash (Computer file); Multimedia systems; Web sites -- Design